TECHNOLOGY-ORGANIZATION-ENVIRONMENT FRAMEWORK: THE ROLE OF DIGITAL FINANCIAL SERVICES IMPLEMENTATION ON MSME PERFORMANCE (STUDY AT TOKYO MARKET AREA, PIK 2) - Thalib, Desinta Arnetti; Zulkarnain (Count : Journal of Accounting, Business and Management, 2023)
Micro, small, and medium enterprises (MSMEs) are crucial to the global economy. The digital transformation in this sector encourages the use of digital financial services such as digital loans and payments. This research uses the Technology, Organization, and Environment (TOE) framework to investigate how digital financial services (DFS) affect the performance of MSMEs in the Tokyo Market area, PIK 2. The study was conducted by distributing questionnaires. Data was collected from MSMEs in the Tokyo Market area between April 2024 and May 2024. Using quantitative methods, the researchers analyzed responses from 83 participants using a structural equation model. The result show that technology and organization influence the adoption of DFS, which the positively impacts MSME performance. However, the environment does not affect the adoption of DFS. Additionally, the adoption of DFS mediates the impact of technology and organization on MSME performance, but does not mediate the impact of the environment on MSME performance. The implications of this research highlight the importance of MSMEs prioritizing the adoption of DFS in the digital era to improve and maintain their performance.